Polyherbal Chewing Gum: A Comprehensive Exploration of Design and Quality for Mouth Ulcers Relief - Dhamai, Kanchan .N.; Jadhao, Dr. M. P.; Game, Dr. M.D.; Jawarkar, S. G.; Waghulkar, V. M. (Asian Journal of Pharmaceutical Research and Development, 2024)
Gummies are mobile drug delivery systems. Extract from herbal medicines can be incorporated into chewing gum and can be used in the treatment of mouth ulcers. It was concluded that the gum is an excellent drug delivery system for self-medication as it is convenient and can be administered directly without water and contain one or more active substances that are released by chewing and are intended for use for local treatment of oral diseases or systemic administration after absorption through the buccal mucosa. Natural a gum base that is economical, safe, environmentally friendly and used in the treatment of various oral diseases.